Antimicrobial peptide 2K4L disrupts the membrane of multidrug-resistant Acinetobacter baumannii and protects mice against sepsis - Ji, Fangyu; Tian, Guoxu; Shang, Dejing; Jiang, Fengquan (Frontiers in Microbiology, 2023)
Antimicrobial peptides represent a promising therapeutic alternative for the treatment of antibiotic-resistant bacterial infections. 2K4L is a rationally-designed analog of a short peptide temporin-1CEc, a natural peptide isolated and purified from the skin secretions of the Chinese brown frog Rana chensinensis by substituting amino acid residues. 2K4L adopt an α-helical confirm in a membrane-mimetic environment and displayed an improved and broad-spectrum antibacterial activity against sensitive and multidrug-resistant Gram-negative and Gram-positive bacterial strains. Here, the action mechanism of 2K4L on multidrug resistant A. baumannii (MRAB) and protection on MRAB-infected mice was investigated. The results demonstrated high bactericidal activity of 2K4L against both a multidrug resistant A. baumannii 0227 strain (MRAB 0227) and a sensitive A. baumannii strain (AB 22934), indicating a potential therapeutic advantage of this peptide. Strong positively-charged residues significantly promoted the electrostatic interaction on 2K4Lwith LPS of the bacterial outer membrane. High hydrophobicity and an α-helical confirm endowed 2K4L remarkably increase the permeability of A. baumannii cytoplasmic membrane by depolarization of membrane potential and disruption of membrane integration, as well as leakage of fluorescein from the liposomes. Additionally, 2K4L at low concentrations inhibited biofilm formation and degraded mature 1-day-old MRAB 0227 biofilms by reducing the expression of biofilm-related genes. In an invasive A. baumannii infection model, 2K4L enhanced the survival of sepsis mice and decreased the production of the proinflammatory cytokines downregulating the phosphorylation level of signaling protein in MAPK and NF-κB signaling pathways, indicating that 2K4L represents a novel therapeutic antibiotic candidate against invasive multidrug-resistant bacterial strain infections.